MLA style manual and guide to scholarly publishing - Gibaldi, Joseph, 1942-; Modern Language Association of America (New York : The Modern Language Association of America, 1998)
Since its publication in 1985, the MLA Style Manual has been the standard guide for graduate students, teachers, and scholars in the humanities and for professional writers in many fields. Extensively reorganized and revised, the second edition contains new sections and updated guidelines on citing electronic works - including sources from the Internet.
1. Scholarly publishing -- 2. Legal issues in scholarly publishing -- 3. Basics of scholarly writing -- 4. Preparation of scholarly manuscripts -- 5. Preparation of theses and dissertations -- 6. Documentation : preparing the list of works cited -- 7. Documentation : citing sources in the text -- 8. Abbreviations -- Appendix. Other systems of documentation.
Includes bibliographical references and index.
Keywords: Authorship -- Style manuals; Humanities literature -- Authorship -- Handbooks, manuals, etc; Scholarly publishing -- Handbooks, manuals, etc; Academic writing -- Handbooks, manuals, etc; Writing -- standards -- Handbooks; Publishing -- standards -- Handbooks